Field survey of foliage-dwelling spiders (Arachnida, Araneae) in Peninsular Malaysia - Dzulhelmi Muhammad Nasir; Suriyanti Su; Badiozaman Sulaiman; Madihah Halim; Nur-Syahirah Mamat; Farah Nadiah Rosli; Faszly Rahim (The Entomological Society of Indonesia, 2024)
Non-Indexed Publication